Selecting the highly skilled: norms and practices of the Swiss admission system for non-EU immigrants - Hercog, Metka; Sandoz, Laure (My University, 2018)
This article problematizes the concept of highly skilled migrants through an analysis of policy documents and interviews with key informants involved in the admission process in Switzerland. Current political discourse classifies foreigners differently according to their country of origin and skill level. Existing legislation prioritizes immigrants from the European Economic Area and is very restrictive towards third-country nationals. By examining the implementation of the admission policy for labour migration, this article evaluates which criteria matter most to state authorities when determining if someone is a desirable immigrant. Despite its stress on qualifications and economic interest, the admission process for third-country workers was also found to fulfil non-economic objectives such as providing the impression of state control over immigration and of state protection of local populations from migrants. Building on this observation, the article argues that more in-depth studies are required to better understand how states reconcile the different objectives of immigration governance in practice.
Keywords: highly skilled migrants; immigration policy; policy implementation; immigration control; Switzerland